The Life Story Board: A Feasibility Study of a Visual Interview Tool for School Counsellors - Chase, Robert M.; Medina, María Fernanda; Mignone, Javier (Canadian Journal of Counselling and Psychotherapy, 2012)
The article describes the findings of a pilot study of the Life Story Board (LSB), a novel visual information system with a play board and sets of magnetic cards designed to be a practical clinical tool for counsellors, therapists, and researchers. The LSB is similar to a multidimensional genogram, and serves as a platform to depict personal narrative information and catalyze verbal and nonverbal approaches in assessment and therapy. A prototype version of the LSB was pilot-tested to assess its clinical feasibility for school counsellors in Winnipeg, Manitoba, working for the most part with newcomer immigrants. Results confirmed that the visual participatory process facilitated rapport with students and elicited useful information. LSB methods may be well suited to assessment and interventions common to schools and in diverse therapeutic and assessment applications.